The Effectiveness of Gojek’s Product Placement in Keluarga Cemara Movie towards Purchase Intention - Anggeliana, Dhea; Alif, Muhammad Gunawan; Pangaribuan, Christian Haposan (Journal of Business, Management, and Social Studies, 2021)
Objective – This study explores the influence of product placement towards purchase intention while assessing the effectiveness of the ad determined by aspects of prominence, celebrity endorsement, modality, attitude towards movie and attitude towards brand.Methodology – This type of research was a quantitative method using associative research approach and measured by regression method. The distribution of questionnaires was a non-probability with simple random sampling. The survey was conducted to 184 respondents in Jakarta, Indonesia, in May 2019.Findings – The research found that modality does have a direct and significant effect on attitude towards the movie, attitude towards the brand, and purchase intention. We also find that celebrity endorsement has an impact on attitude towards the brand and purchase intention, not on attitude towards the movie. Prominence does not seem to have any relationship with all dependent variables.Novelty – Although research has investigated product/brand placement, we extend the literature by investigating modality, prominence, and celebrity endorsement.